Stock Market Movements - A Comparative Analysis on Growth Patterns in India’s Leading Stock Exchange - Lawrence, Arun; Thattil, Gabriel Simon; Antony, Tom; Ittoop, Jeena (International Journal of Economics and Financial Issues, 2025)
Growth in the financial market need not always get reflected in terms of earnings growth for investors. Certain sectors and certain class of investors could remain beyond the growth story. It is thus essential to examine whether growth in the Indian financial market are reflected in terms of real time gains in leading financial indices. The leading stock market institution of the country namely National Stock Exchange (NSE) and its sectoral indices from the subject matter of analysis. This study analyses the gains and performance trends of the Indian financial market over the past decade, focusing on the NSE Nifty and its key sectoral indices—Nifty IT, Nifty Energy, Nifty Infrastructure, and Nifty Bank. Utilizing secondary data from April 2014 to March 2024, the research employs month-to-month and year-to-year change benchmarks to assess index performance and applies the Concurrent Deviation Method to evaluate correlations between indices. The findings reveal overall resilience and growth, with significant recoveries following downturns such as the 2015-16 economic slump and the COVID-19 pandemic. Notable positive performances were observed across indices, with Nifty IT and Nifty Energy showing substantial gains in the aftermath of the pandemic. The study also highlights strong positive correlations among the indices, indicating interdependence in market movements. Looking forward, the Indian financial market is expected to benefit from government policies and sectoral trends, particularly in clean energy and infrastructure, while global economic conditions and investor sentiment will continue to influence market dynamics. Investors can leverage the findings of this study to make informed decisions and capitalize on strong growth potential.